De tidlige trekirkenes planlegging og design: Et bidrag til en teoridannelse - Jensenius, Jørgen H. (Hikuin, 2003)
Planning and Design of the Early Wooden Churches. A Contribution to a Theory By Jørgen H. Jensenius. For more than 160 years, researchers have conducted investigations into the churches which existed before the stave churches in Norway, and they have pointed out possible prototypes both at home and abroad. However, theories relating to origins often deal only with external form. In my dissertation (Jensenius 2001) the conclusion reveals that church building was part of an experiencebased tradition wherein knowledge about the buildings’ visible and invisible order (measurements) was transferred from prototypes through imitation of a series of actions.